2001
DOI: 10.1046/j.1472-765x.2001.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Lactobacillus helveticus strain CP53 in the human gastrointestinal tract

Abstract: A strain of Lactobacillus helveticus carrying the cryptic plasmid pCP53 was used for a detailed analysis of the survival and persistence of this organism in the faeces of volunteers administered oral doses of the strain. The CP53 strain had high af®nity for Caco-2 cells, but displayed low bile acid resistance in vitro. Rifampicin-resistant colonies could be reisolated from the faeces of four of seven subjects fed with the rifampicin-resistant CP53 derivative strain. Moreover, the recovery of cells, as estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
1
Order By: Relevance
“…Moreover, in previous studies of probiotic lactobacilli, the numbers of lactobacilli re‐isolated from feces were as follows: 10 6.8 cells g −1 of feces for L. casei strain Shirota [2], 10 7.7 cfu g −1 of feces for Lactobacillus sp. strain GG [3], 10 6.7 cells (one time feces) −1 for L. helveticus strain CP53‐R [4]. These strains could not be detected at a level comparable to the ingestion level, even if the lactobacilli were probiotics.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, in previous studies of probiotic lactobacilli, the numbers of lactobacilli re‐isolated from feces were as follows: 10 6.8 cells g −1 of feces for L. casei strain Shirota [2], 10 7.7 cfu g −1 of feces for Lactobacillus sp. strain GG [3], 10 6.7 cells (one time feces) −1 for L. helveticus strain CP53‐R [4]. These strains could not be detected at a level comparable to the ingestion level, even if the lactobacilli were probiotics.…”
Section: Resultsmentioning
confidence: 94%
“…The potential use of probiotics requires the investigation of the viability of these strains in the gastrointestinal tract. In many cases, re‐isolation of a particular strain from the feces of volunteers by the culture method has demonstrated that the ingested bacterial cells can survive through the gastrointestinal tract [2–4]. However, the ratio of lactobacilli in the fecal microflora is relatively low, even though lactobacilli are major bacteria in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…If the number of enterococci recovered had been decreased, greater Lactobacillus strain diversity may have been revealed. Rif r marking to recover introduced Lactobacillus strains from the indigenous GIT microbiota has been successfully used in chickens (23,43), ducks (16), pigs (22,39), mice (19,41), and humans (20,45), so a Rif r background was unexpected in this study. Rif MIC levels within several Lactobacillus and Pediococcus species have been reported to range between Յ0.016 and 4 g ml Ϫ1 (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Ten microliters of the cell suspension was inoculated in a 96-well plate containing 190 μl of MRS added with different concentrations of each bile salt and then incubated for 24 h at 45°C. After incubation, Abs 600 was measured and the results were expressed as the percentage of growth in the presence of bile salts compared to the control grown without the addition of any compound (Shinoda et al, 2001).…”
Section: Methodsmentioning
confidence: 99%